MARCKS regulates neuritogenesis and interacts with a CDC42 signaling network - Brudvig, J. J. (Sci Rep, 2018)
Through the process of neuronal differentiation, newly born neurons change from simple, spherical cells to complex, sprawling cells with many highly branched processes. One of the first stages in this process is neurite initiation, wherein cytoskeletal modifications facilitate membrane protrusion and extension from the cell body. Hundreds of actin modulators and microtubule-binding proteins are known to be involved in this process, but relatively little is known about how upstream regulators bring these complex networks together at discrete locations to produce neurites. Here, we show that Myristoylated alanine-rich C kinase substrate (MARCKS) participates in this process. Marcks(−/−) cortical neurons extend fewer neurites and have less complex neurite arborization patterns. We use an in vitro proteomics screen to identify MARCKS interactors in developing neurites and characterize an interaction between MARCKS and a CDC42-centered network. While the presence of MARCKS does not affect whole brain levels of activated or total CDC42, we propose that MARCKS is uniquely positioned to regulate CDC42 localization and interactions within specialized cellular compartments, such as nascent neurites.